Chapter 9 THE CARE DEPENDENCY GRANT IN SOUTH AFRICA Challenges on the Road to Inclusive Rights - Trafford, Zara (Taylor & Francis, 2023)
State-funded social protection can assist poor families in providing for disabled children, especially in the global south where most of the world's disabled population lives. This chapter is a case study of the South African care dependency grant, a social assistance cash transfer available to caregivers of disabled children. The programme is strong in principle but insufficient access and poor implementation have limited progress toward CRC and CRPD obligations. There is an urgent need for attitudinal change, effective intersectoral collaboration and practical (rather than symbolic) commitments to disabled children as full rights-holders. Insights are relevant to those interested in social protection for disabled children in the global south and in the north, where austerity measures threaten earlier progress.